PENGEMBANGAN MEDIA FILM DOKUMENTER BERBANTUAN APLIKASI INSHOT PADA MATA PELAJARAN SEJARAH MATERI PRA SEJARAH DI NUSANTARA - Putri Ramadhani; Zulfa; Liza Husnita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
In the History subject for class x at SMAN 16 Padang, the use of available learning media is very limited during the learning process. Students' interest in what they are learning is low and this results in students becoming bored while studying and looking for other activities. Students are less involved in the teaching and learning process. Therefore, there is a need for interesting learning media, to make it easier for students in the learning process. One type of learning media that is considered to be able to overcome several obstacles in the learning process is documentary film learning media. The aim of this research is to develop documentary film learning media for Class X history subjects at SMAN 16 Padang that is valid and practical. This research uses the Research and Development (R & D) research and development method with the ADDIE development model which has 5 stages, namely Analysis, Design, Development, Implementation and Evaluation. Research subjects to measure the validity of test media with media validators. The media validators involved are 1 media expert and 1 material expert. The research subjects for testing the practicality of documentary film learning media in history subjects using the Inshot application were class X students at SMAN 16 Padang, totaling 35 student responses and 1 teacher response as a test subject. Data collection techniques are in the form of observation and questionnaires, while the data collection instrument is a validity questionnaire. The data analysis technique uses a Likert scale. The results of this research show that the validity value of the media is an average of 97.5 in the